Hereditary Hemorrhagic Telangiectasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Hereditary Hemorrhagic Telangiectasia (HHT), also known as Osler-Weber-Rendu disease, was the subject of an NIH workshop, organized by the National Heart, Lung, and Blood Institute, on July 10-11, 1997.